2014
DOI: 10.4317/jced.51318
|View full text |Cite
|
Sign up to set email alerts
|

Areca nut and its role in oral submucous fibrosis

Abstract: Areca nut, commonly called as betel nut or supari, is a fruit of areca catechu palm tree, which is native of South Asia and Pacific Islands. The seed or endosperm is consumed fresh, boiled or after sun drying or curing. Chewing areca nut is thought to have central nervous system stimulating effect and along with this it is known to have salivary stimulating and digestive properties. According to the traditional Ayurvedic medicine, chewing areca nut and betel leaf is a good remedy against halitosis. It is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 36 publications
0
79
0
2
Order By: Relevance
“…This indicated that at certain point, the damage caused by BQ may be too severe or irreversible for BQ cessation to overcome. For example, BQ is a major risk factor for oral submucous fibrosis, an irreversible potentially malignant disorder that is characterized by juxta-epithelial inflammation and progressive fibrosis of the submucosal tissues [16]. The malignant transformation rate of OSF was estimated at 7.6% for a follow-up period of 17 years [17].…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that at certain point, the damage caused by BQ may be too severe or irreversible for BQ cessation to overcome. For example, BQ is a major risk factor for oral submucous fibrosis, an irreversible potentially malignant disorder that is characterized by juxta-epithelial inflammation and progressive fibrosis of the submucosal tissues [16]. The malignant transformation rate of OSF was estimated at 7.6% for a follow-up period of 17 years [17].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, current investigations indicated that the most serious side-effects of arecoline are the oral toxicities Chen et al 2014). Oral submucous fibrosis (OSF) is a potentially malignant disease predominantly seen in people of Asian; epidemiological surveys provide valid evidence that chewing AN can lead to OSF, and arecoline is the main etiological factor (Prabhu et al 2014;Hosein et al 2015). It could interfere with the molecular processes of deposition and/or degradation of extracellular matrix (ECM) molecules, such as collagen, causing imbalance in the normal process (Utsunomiya et al 2005;Tilakaratne et al 2006;Arakeri & Brennan 2013).…”
Section: Toxicologymentioning
confidence: 99%
“…Oral submucous fibrosis (OSF) is a chronic debilitating disease of the oral mucosa with a high risk of malignant transformation. OSF is mainly associated with the practice of betel quid chewing . Hence, OSF is predominantly seen in population groups from South and Southeast Asia .…”
Section: Introductionmentioning
confidence: 99%
“…OSF is mainly associated with the practice of betel quid chewing . Hence, OSF is predominantly seen in population groups from South and Southeast Asia . OSF usually affects young individuals aged 20‐40 years old, with a striking male predilection, and an estimated prevalence of 6.42 per 1000 .…”
Section: Introductionmentioning
confidence: 99%